La preservación audiovisual en América Latina - Cuarterolo, Andrea; Nagime, Mateus (Imagofagia, 2021)
Introducción al dossier "La preservación audiovisual en América Latina" Resumo: Introdução ao dossiê " A preservação audiovisual na América Latina" Abstract: Introduction to the dossier "The Audiovisual Preservation in Latin America”